Compression and evaluation of extended release matrix pellets prepared by the extrusion/spheronization process into disintegrating tablets - Raveendra Pai; Kanchan Kohli; Birendra Shrivastava (Universidade de São Paulo, 2012)
In this study, a novel approach for compression of matrix pellets into disintegrating tablets has been studied in an attempt to overcome the issues pertaining to rupture of polymer coat during compression of reservoir-type pellets. Extended release matrix pellets were prepared by the extrusion/spheronization technique using commercially available aqueous dispersions of ethyl cellulose, acrylic polymers and sodium alginate at 10%, 20% and 30%w/w levels. Sertraline hydrochloride was used as the model drug and an in vitro release profile of 12 h was targeted. Tablets containing matrix pellets were prepared by the direct compression process. Acceptance Value, a pharmacopeial test, was applied to study the uniformity of drug distribution. Effect of compression force (2-6 kN), extrusion screen aperture size, diluent blend composition and pellet percentage on drug release and acceptance value were studied. As polymer is uniformly distributed within each pellet, the drug release pattern from uncompressed pellets was comparable to compressed tablets. Surface morphological changes due to calcium chloride treatment were observed using Scanning electron microscopy. The pellet segregated from the surface of the tablet was found to be flattened in the direction of applied compression force with minor deformities. In conclusion, matrix pellets can constitute an alternative approach to reservoir-type pellets in obtaining disintegrating tablets for extended delivery of drugs. Nesse trabalho, estudou-se nova abordagem para a compressão de matrizes de péletes em comprimidos desintegrantes, com o intuito de resolver os problemas relativos à ruptura do polímero de revestimento durante a compressão dos péletes do tipo reservatório. Matrizes de péletes de liberação estendida foram preparadas pela técnica de extrusão/esferonização, utilizando dispersões aquosas comercialmente disponíveis de etil celulose, polímeros acrílicos e alginato de sódio a 10%, 20% e 30% p/p. O cloridrato de sertralina foi utilizado como fármaco modelo e focalizou-se no perfil de liberação in vitro de 12 horas. Os comprimidos contendo matrizes de péletes foram preparados pelo processo de compressão direta. O valor de aceitação, teste farmacopéico, foi aplicado para estudar a uniformidade de distribuição do fármaco. O efeito da força de compressão (2-6 kN), o tamanho da abertura de extrusão, a composição da mistura diluente, a porcentagem de pélete na liberação de fármaco e o valor de aceitação foram estudados. Como o polímero é uniformemente distribuído dentro de cada pélete, o padrão de liberação do fármaco dos péletes não-comprimidos foi comparável àquele dos comprimidos. As mudanças morfológicas da superfície devidas ao tratamento com cloreto de cálcio foram observadas utilizando-se a microscopia eletrônica de varredura. O pélete segregado da superfície do comprimido mostrou-se plano em direção à força de compressão aplicada com menores deformidades. Em conclusão, os péletes matriz podem se constituir em abordagem alternativa para péletes do tipo reservatório na obtenção de comprimidos desintegrantes para fármacos de liberação estendida.